Insecticidal, Repellent and Antifeedant Activity of Essential Oils from Blepharocalyx cruckshanksii (Hook. & Arn.) Nied. Leaves and Pilgerodendron uviferum (D. Don) Florin Heartwood against Horn Flies, Haematobia irritans (Diptera: Muscidae) - Javier Espinoza (MDPI AG, 2021)
Haematobia irritans is a cosmopolitan obligate blood-feeding ectoparasite of cattle and is the major global pest of livestock production. Currently, H. irritans management is largely dependent on broad-spectrum pesticides, which has led to the development of insecticide resistance. Thus, alternative control methods are needed. Essential oils have been studied as an alternative due to their wide spectrum of biological activities against insects. Thus, the main aim of this study was to evaluate the insecticidal, repellent and antifeedant activity of the essential oils from Blepharocalyx cruckshanksii leaves and Pilgerodendron uviferum heartwood against horn flies in laboratory conditions. The composition of the essential oils was analyzed using gas chromatography coupled to mass spectrometry. Accordingly, α-pinene (36.50%) and limonene (20.50%) were the principal components of the B. cruckchanksii essential oil, and δ-cadinol (24.16%), cubenol (22.64%), 15-copaenol (15.46%) and δ-cadinene (10.81%) were the most abundant compounds in the P. uviferum essential oil. Mortality of flies and feeding behavior were evaluated by non-choice tests, and olfactory response was evaluated using a Y-tube olfactometer. Both essential oils were toxic to horn flies, with LC50 values for B. cruckchanksii essential oil of 3.58 µL L−1 air at 4 h, and for P. uviferum essential oil of 9.41 µL L−1 air and 1.02 µL L−1 air at 1 and 4 h, respectively. Moreover, the essential oils exhibited spatial repellency in the olfactometer using only 10 µg of each oil, and these significantly reduced the horn fly feeding at all doses evaluated. Although further laboratory and field studies related to the insectistatic and insecticide properties of these essential oils against H. irritans are necessary, B. cruckshanksii leaves and P. uviferum heartwood essential oils are promising candidates for horn fly management.